(untitled) (Italian Journal of Public Health, 2012)
Background: Between May 2010 and october 2011 the unit of Preventive Medicine for the developmental ages of district IV, Health unit aSL rM/a, received 136 measles case notifications from the unit of Epidemiology and Prophylaxis of Infectious diseases. MEtHodS: In accordance with the infectious diseases monitoring protocol, we introduced a series of preventive measures, such as monitoring subjects in contact with measles-infected patients, recommend- ing the administration of two Measles Mumps and rubella (MMr) doses four weeks apart, and informing paediatricians, families and school teachers about the measles epidemic. rESuLtS: all the activities above led to an increased number of MMr doses administered and a significant improvement of measles immunization coverage among residents of the district IV health unit of rome. concerning MMr 1, in a sample cohort consisting of children ≤24 months, the immunization coverage increased from 77% on the 31/12/09 to 88% on the 31/12/11. Instead, for MMr 2, in a cohort of children ≤6 years, the same ratio improved from 51% on the 31/12/09 to 65% on the 31/12/11. dIScuSSIon: the results indicate a material increase in the immunization coverage once our public health actions and vaccination strategies had been implemented among young residents of district IV aSL rM/a.